A high-efficient and fast-transient buck-boost converter using adaptive direct path skipping and on-duty modulation. (December 2017) - Jung, Young-Ho; Hong, Seong-Kwan; Kwon, Oh-Kyong
Abstract: This paper proposes a high-efficient and fast-transient buck-boost DC-DC converter for battery-powered mobile devices. The proposed converter employs an adaptive direct path skipping to minimize the switching losses caused by power transistors, and thus enhances the power efficiency and extends the usage time of the mobile device. It also adopts an on-duty modulation to achieve a fast line transient response, thereby rapidly regulating its output voltage. The proposed buck-boost converter was fabricated using 0.18-μm CMOS process technology with 1.8 V and 6.0 V CMOS devices. The measurement results show that the maximum power efficiency is achieved up to 97.6% at a load current of 100 mA. In addition, the measured line transient response is 155 μs/V.